Study of PH and Electrical Conductivity in Soil of Barnala District (Punjab, India): Deleterious Effects on Human Lives - Kaur, Dr. Kamalpreet (Discoveries in Agriculture and Food Sciences, 2019)
The purpose of this study was to determine the pH and electrical conductivity in soil of different villages of barnala district (Punjab,India ) and their harmful effects on human health. Samples of soil were collected from agricultural fields of four different villages of barnala region such as Rure ke kalan, Gunas, Handiaya and cheema from five different layers(0-10 cm; 10-20 cm; 20-30 cm; 30-40 cm and 40-50 cm depth).There are three industrial sites in barnala district and these four villages are located near to these industial sites. In this study, adverse effect of different industries on fields of these four villages were investigated. Handiaya village has high values of pH and electrical conductivity while Gunas and Cheema villages have lowest value of electrical conductivity and pH respectively. when textile effluent reaches the soil or underground water it causes bad effect on human health such as people may suffer from alkalosis which is due to high pH and can lead to arrhythmia which means irregular heartbeat. Alkalosis can induce a coma, it may cause seizures and malfunctioning of kidneys. Due to large value of Electrical conductivity activity of soil micro-organism declines so, the important microbial processes, such as nitrogen cycling, production of nitrous and other N oxide gases, respiration, and decomposition; populations of plant-parasitic nematodes can increase; and increased nitrogen losses.